Meningkatkan Kemampuan Mengenal Huruf Konsonan Melalui Metode VAKT pada Anak Disabilitas Intelektual Ringan (Single Subject Research di Kelas V SLB Negeri 1 Muaro Sijunjung) - Oktariza, Adrea; Zulmiyetri, Zulmiyetri; Budi, Setia; Safaruddin, Safaruddin; Yuliana, Syari (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the ability to recognize consonants using the VAKT method. The method used is a quantitative method with an experimental research type in the form of a single subject research (SSR) using an A-B design. The subjects in this study were children with mild intellectual disabilities in grade V at SLBN 1 Muaro Sijunjung. The data collection technique in this study was a test consisting of several questions. The data obtained were then analyzed using visual graphic analysis techniques. The results showed that the ability to recognize consonants in children in the baseline condition (A) obtained a percentage of 26.7%, 26.7%, 26.7%. In the intervention condition (B) obtained a percentage of 66.7%, 66.7%, 73.3%, 80%, 86.7%, 86.7%, 86.7%. Based on the results of the data analysis, it can be concluded that the ability to recognize consonants in children with mild intellectual disabilities has increased after using the VAKT method.